Analisis Strategi Guru Dalam Meningkatkan Karakter Siswa Kelas 10 Di Sekolah Sma Negeri 1 Labuhan Deli Jalan Serbaguna Ujung Pasar Iv Helvetia - Pakpahan, Amelia Susanti; Sihaloho, Meria Yustinus; Ambarita, Syntia Febriani; Siagian, Vanessa Dwi Putri (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
This study explores how teachers implement strategies to strengthen students’ character development among tenth-grade students at SMA Negeri 1 Labuhan Deli, focusing on aspects such as politeness, responsibility, discipline, cooperation, and honesty. A descriptive qualitative approach was employed, with data collected through interviews with one teacher and three students, classroom observations integrating character education, and supporting documentation. The findings reveal that teachers apply several strategies, including modeling positive behavior, establishing character-based routines, providing personal guidance, implementing reward and punishment systems, and involving parents. These strategies have led to positive behavioral changes students have become more polite, responsible, and disciplined although some still require continuous guidance. The study concludes that consistent teacher practice and strong collaboration between schools and families are key factors in effective character formation